2017
DOI: 10.11118/actaun201765020391
|View full text |Cite
|
Sign up to set email alerts
|

Basic Thermal Parameters of Selected Foods and Food Raw Materials

Abstract: In general, processing and manipulation with foods and food raw materials have significant influence on their physical properties. The article is focused on thermophysical parameters measurement of selected foods and food raw materials. There were examined thermal conductivity and thermal diffusivity of selected materials. For detection of thermal parameters was used instrument Isomet 2104, which principle of measurement is based on transient methods. In text are presented summary results of thermal parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 3 publications
0
3
0
2
Order By: Relevance
“…However, it was enhanced by blanching and boiling the anchote tuber before making the flour. The variation in Cp of the flours might be due to the moisture content difference and change in its composition by the pretreatments (Božiková, Híreš, Valach, Malínek, & Mareček, 2017). The finding showed that Cp of anchote flour is similar to that of cocoyam flour (1.744–1.785 kJ/kg o C) (Ajala et al., 2014) and flours of plantain cultivars (1.67–1.7 kJ/kg o C) (Barine & Victor, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it was enhanced by blanching and boiling the anchote tuber before making the flour. The variation in Cp of the flours might be due to the moisture content difference and change in its composition by the pretreatments (Božiková, Híreš, Valach, Malínek, & Mareček, 2017). The finding showed that Cp of anchote flour is similar to that of cocoyam flour (1.744–1.785 kJ/kg o C) (Ajala et al., 2014) and flours of plantain cultivars (1.67–1.7 kJ/kg o C) (Barine & Victor, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…having the highest value than lowest value for raw sample dried at 100°C (Table 3) (Božiková, Híreš, Valach, Malínek, & Mareček, 2017).…”
Section: Specific Heat Capacity (Cp)mentioning
confidence: 98%
“…Значения величины температуропроводности высушенного измельченного жмыха плодов облепихи определяли расчётным путем, зная величину его плотности по отношению значения теплопроводности жмыха к произведению удельной теплоемкости и плотности, измеренных в одинаковых условиях [6].…”
Section: материалы и методыunclassified
“…ε"= 5,504194 -0,314878 • t + 0,647321×W c + + 0,02905 t 2 -0,011042 W c2 (6) Обсуждение Удельная массовая теплоемкость с увеличением влажности жмыха повышается, поскольку доля воды, имеющая теплоемкость гораздо большую по сравнению с сухим остатком и облепиховым маслом в жмыхе.…”
Section: материалы и методыunclassified
“…Most food materials are made up of complicated structure which leads to the changeability of their physical, biological and chemical properties especially when heat is applied. One of the primary tasks of food industry is obtain knowledge about the thermo-physical parameters of the food material due to the continuous change in the food structure during processing (Bozikova et al, 2017). Therefore, the thermal properties of food 10.2478/aucft-2021-0023 using artificial neural network have ample importance in food process engineering.…”
Section: Introductionmentioning
confidence: 99%